Bookman Solomon Dolnik: A Zionist between Zionists - G. S. Zelenina (Шаги, 2025)
The article examines the life-story and autobiographical writing of Solomon Borisovich Dolnik (1901–1986), a Jewish activist in the Soviet Union who practically single-handedly engaged in underground Zionist samizdat during 1960–1966 and was sentenced to four years in a labor camp for “anti-Soviet agitation and propaganda.” The article examines both the controversial aspects of Dolnik’s biography — his relationship with other activists before and after his trial, the actual reasons for his conviction, the background for the uncordial reception he received in Israel — and the idiosyncrasies of his conception of himself and his life writing. The article is primarily intended to highlight a forgotten historical figure, restoring another page in the history of the Jewish national movement in the USSR, the beginning of which, due to the almost complete replacement of the activist cohorts, is usually attributed to a later period. In addition, some observations are made as to how Dolnik (and this might be applicable to other Zionists of his generation) assessed the Jewish destiny in the USSR, the disposition of his fellow Jews, the abilities and determination of Jewish youth and activists among them. Another focus of the paper is the way Dolnik has constructed his autobiographies as both a manifesto, a polemics, an accusation, and an auto-apology.